Design of antimicrobial composite nanoparticles ZnxMe(100-x)/O by electrical explosion of two wires in the oxygen-containing atmosphere. (5th December 2019) - Lozhkomoev, A.S.; Kazantsev, S.O.; Kondranova, A.M.; Fomenko, A.N.; Pervikov, A.V.; Rodkevich, N.G.; Bakina, O.V.
Abstract: The problem of formation of resistant strains of bacteria contributes to the development of the fields related to nanoparticles that can become the alternatives of antibiotics. The composite zinc oxide based nanoparticles produced by electrical explosion of two twisted Zn/Al, Zn/Ag, Zn/Cu, Zn/Ti wires in the oxygen-containing atmosphere have been demonstrated to exhibit more pronounced antibacterial action with regard to Gram-positive MRSA and Gram-negative E. coli as compared to nanoparticles produced in the same conditions by the electrical explosion of single Zn, Al, Cu, Ag and Ti wires. The composite Zn55Ag45/O and Zn55Cu45/O nanoparticles have been shown to possess the most antibacterial activity. The nanoparticles have been established to possess similar size distribution and positive zeta potential. The nanoparticles can consist of a mixture of oxides, or a mixture of oxides and spinel type ZnAl2 O4 or Zn2 TiO4, as well as of zinc oxide and Ag. Graphical abstract: Unlabelled Image Highlights: Composite nanoparticles of different composition can be obtained by electrical explosion of two wires. The antibacterial activity of oxide composite nanoparticles exceeds the activity of monoxide nanoparticles by 3–4 times. Minimal inhibition concentration of MRSA of Zn55Cu45/O and Zn55Ag45/O nanoparticles is 250 μg/ml.